Urban Inequality - Jesús Manuel González Pérez (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
After the impact of the 2007 crisis and post-crisis austerity policies, cities are being reconfigured under the auspices of inequality. The objective of this book is to study inequality in the city at different scales and in all territories, from informal settlements and the "urbanization of poverty" in the countries of the South, to the fragmentation of the city or urban segregation as global phenomena in 21st century cities. In line with this, we propose introducing new debates on the city and inequality linked to social movements, urban governance, and the access to and quality of drinking water, among other topics. The issue includes articles on social movements and resistance in Latin American cities, vulnerability in crisis-hit Spanish cities, and the segregation and quality of basic services in US cities.